The Education Inspectorate: part of the solution or part of the problem? - Díaz Rodríguez, Vicente; Carrasco Embuena, Vicente (Avances en Supervisión Educativa, 2011)
This article posits that education inspectors in Spain have become part of the many problems ailing the Spanish Educational system, especially those related to its comprehensiveness and the qualifications it issues. It reviews the main traits of the inspectors’ weak professional code, which holds a close relationship with some features of the Spanish school system. The author believes the latter features are the origin of the above-mentioned problems. Finally, a set of measures is suggested that may eventually change the current role of education inspectors. These measures may, according to the author, help education inspectors become part of a solution for Spanish schools.